PERAN UNITED NATIONS DEVELOPMENT PROGRAMME (UNDP) DALAM MELEGALKAN PERNIKAHANLESBIAN, GAY, BISEXUAL,TRANSGENDER( LGBT ) DI TIONGKOK - Aira Tama; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study attempts to outline anything program-program undp in legalising lgbt marriage in china.And also will explain how program-program undp in legalising lgbt marriage in china.The methodology used is qualitative study.This study focused to talk about the role in the United Nations DeveopmentProgram ( UNDP ) legalising lgbt in the country tiongkok. Second, researchers feel the need to give time limit to phenomena or problem to check such as in 2014-2016This research use a pluralism perspective and international organizations theory. The level analysis is international organizations, this reseach also includes the concept of human rights as the point of views this research.The result of this research UNDP support lesbian community , gay , bisexual , and transgender ( LGBT ) Community to get the rights one of which is a same-sex marriage.Keywords: United Nations Deveopment Programme (UNDP), LGBT, Same Marriage, Tiongkok